Bolsa Família, occupational choice and informality in Brazil - Ana Luiza Neves de Holanda Barbosa; Carlos Henrique L. Corseuil (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
This study analyses the impact of the conditional cash transfer programme, Programa Bolsa Família, on the occupational composition of the Brazilian labour market. The methodology relies on a discontinuity in the programme eligibility rule regarding children's age to attain the identification of a LATE parameter. The analysis is carried out with 2006 microdata from the National Household Sample Survey (PNAD). Our results suggest that the cash transfer does not affect the occupational choice of Brazilian adults among formal and informal jobs.
Keywords: I38; O17; 330; Income transfer; informal labour; regression discontinuity design